Supramolecular interactions from small-molecule selectivity to molecular capsules - Rajbanshi, Arbin (Kansas State University, 2010)
Supramolecular synthesis relies upon the creative and rational use of the common intermolecular forces and a proper understanding of these forces is critical for design and assembly of molecular building blocks into extended networks. The strength of seven substituted pyridines as hydrogen-bond acceptors was probed using a series of fifteen mono/dicarboxylic acids to demonstrate the interrelationship between the charge on the substrate and its ability to form co-crystals/salts. The higher charge in the acceptor led to proton transfer (100% yield) from the hydrogen bond donor to give a salt, whereas the lower charge led to co-crystals. This specificity observed for small molecules was extended to an investigation of selectivity in ditopic molecules. A series of nineteen hydrogen-bond donors, including fifteen carboxylic acids and four cyanoximes, were tested for binding preferences against ten ditopic ligands with variable charges. The overall supramolecular yield of 82% (9/11) proved a high degree of reliability in terms of best acceptor/donor approach, hence establishing the efficiency of the calculated charges as a guideline for molecular recognition processes. Solubility and thermal properties of pharmaceutical drug mimics were altered via formation of co-crystals/salts. The ligands and their co-crystals/salts with five even-chain dicarboxylic acids were synthesized and their comparative solubility in pure water and in pH 6.8 buffer solution measured. Solubility enhancement to a degree of 9x is observed for pharmaceutical drug haloperidol, whereas decrease in solubility down to 81% is achieved for 2-amino-5-(3-pyridyl)pyrimidine (which has agrochemical significance). Also the thermal and solubility behavior of these co-crystals were shown to reflect the properties of their parent co-crystallizing agents, allowing for a modulation of physical properties. Finally, the specificity and selectivity of the intermolecular interactions observed for small molecules were applied in the synthesis of hydrogen and halogen-bonded capsules. Several resorcinarene-based cavitands were synthesized and their upper rim decorated with acetamidopyridyl, aminopyrazinyl, 3-pyridyl, and 4-pyridyl moieties with hydrogen and halogen-bonding potentials. A homomeric hydrogen-bonded capsule was formed with self-assembly of acetamidoethynylcavitand via N-H···O=C interactions, whereas a heteromeric halogen-bonded capsule, the very first of its kind, was formed with N···I halogen-bonded interaction between 3-pyridylcavitand and tetrafluoroiodo-substituted calixarene.
Keywords: co-crystals; supramolecular chemistry; molecular capsules; cavitands; solubility; molecular recognition; Chemistry, Organic (0490)